Nutrients and clam contamination by Escherichia coli in a meso-tidal coastal lagoon: Seasonal variation in counter cycle to external sources. Issue 1 (15th July 2015) - Botelho, Maria João; Soares, Florbela; Matias, Domitília; Vale, Carlos
Highlights: Sources of nutrients and E. coli in Ria Formosa linked to tourism in summer. Lower nutrient values and clam contamination by E. coli in summer. Bactericide effect of temperature and solar radiation causes lower E. coli . Higher biological consumption of nutrients in warmer periods. Results mirror possible effects of climate changes on coastal lagoons. Abstract: The clam Ruditapes decussatus was transplanted from a natural recruitment area of Ria Formosa to three sites, surveyed for nutrients in water and sediments. Specimens were sampled monthly for determination of Escherichia coli, condition index and gonadal index. Higher nutrient values in low tide reflect drainage, anthropogenic sources or sediment regeneration, emphasising the importance of water mixing in the entire lagoon driven by the tide. Despite the increase of effluent discharges in summer due to tourism, nutrient concentrations and E. coli in clams were lower in warmer periods. The bactericide effect of temperature and solar radiation was better defined in clams from the inlet channel site than from sites closer to urban effluents. High temperature in summer and torrential freshwater inputs to Ria Formosa may anticipate climate change scenarios for south Europe. Seasonal variation of nutrients and clam contamination may thus point to possible alterations in coastal lagoons and their ecosystem services.